The Influence of Good Corporate Governance and Financial Performance on Financial Distress During a Pandemic - Suharmadi SUHARMADI; Suripto SURIPTO (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study aims to know the influence of good corporate governance consisting of managing ownership and board of directors and financial performance consisting of profitability ratio and leverage ratio against financial distress on retail companies listed onthe Indonesian stock exchange in 2019-2021. The data collection technique in this study is secondary data. Sampling in this study uses the method of purposive sampling. There are 32 retail companies listed on the Indonesian stock exchange and 26 companies that meet the criteria were obtained, so in 3 years of research 78 data were obtained to be used as research samples. This research was done with the help of the data processing software SPSS (Statistical Package For Social Science) version 26. The method of analysis used is logistic regression analysis. The results of this study prove that managerial ownership (MNJR) has negative effect and not significant on financial distress, the Board of Directors has negative effect and significant on financial distress. Profitability Ratio (ROA) has negative effect but not significant on financial distress. While the leverage ratio (DAR) has positive effect significant on financial distress in retail companies listed on the Indonesia Stock Exchange for the period 2019 – 2021.